FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKTIVITAS KINERJA PEGAWAI SEKRETARIAT DAERAH KABUPATEN SUMBA TENGAH - Andrias Umbu Tuku Anabuni (Journal of Management Small and Medium Enterprises (SMEs), 2016)
This research aimed to investigate the factors influencing the employees working productivity at theSecretariat Division of West Sumba Regency. Some variables considered as the influencing factorstoward the Employees Working Productivity (Y) in this study were the Leadership Style (X3),Working Motivation (X2) and Education and Training (X1). The samples were 60 employeestaken from the population of 210 employees working as staff members at the Secretariat Division ofWest Sumba Regency. Using Multiple Linear Regresion Analysis, the results of the study indicatedthat the Leadership Style (X3), Working Motivation (X2) and Education and Training (X1)influenced the Employees Working Productivity (Y) at the Secretariat Division West SumbaRegency, with coefficient determination was 25,9%, while the rest of 74,1% was contributed byother factors excluded in this study.Keywords : Education and Training, Working Motivation ,Leadreship Style, Employees WorkingProductivity